Distingsi Teologis antara Hukum Musa dan Sepuluh Hukum Tuhan: Sebuah Kajian Reinterpretatif - Gulo, Rezeki Putra; Silaen, Riste Tioma; Zai, Erwin; Mbelanggedo, Nelci (Jurnal Teologi Kontekstual Indonesia, 2024)
This research employs a qualitative research method with a literature review approach. The reinterpretation of the differences between the Law of Moses and the Ten Commandments is an effort to contribute to the discourse on the growing misconceptions about the Law, which significantly deviate from biblical truth. The Old and New Testaments speak of two distinct laws: the Law of Moses and the Ten Commandments of God. Unfortunately, many Christians are unaware of this truth, leading to misconceptions about the definition of the Law that do not align with the Word of God. Based on the research findings, these two "laws" exhibit significant differences: the Law of Moses was temporary, meaning its validity lasted only until the death of Jesus on the cross. In contrast, the Ten Commandments of God represent the Law of Love, given to His people as an eternal principle and standard of life. Thus, the existence of Christ and His Ten Commandments is the central foundation of both the Old and New Testaments. Therefore, the Bible must be comprehensively understood as a unified whole, possessing equal authority.